Neogeografía, Big Data y TIG: problemas y nuevas posibilidades = Neogeography, Big Data and TIG: problems and possibilities - Bosque Sendra, Joaquín (Polígonos. Revista de Geografía, 2015)
La Neogeografía y el BIG data están cambiando la manera de investigar en Geografía, el desarrollo de estos enfoques se basa mucho en la aparición de novedades tecnológicas, en particular de nuevas tecnologías de la información geográfica: GPS, SIG, etc. The Neogeography and the BIG data are changing the way research in geog-raphy, the development of this approach is very much based on the emergence of new technol-ogies, in particular in new technologies of geographic information: GPS, GIS, etc.